Substance-Related Found-Down Compartment Syndrome: A Systematic Review. Issue 7 (July 2021) - Mortensen, Sharri J.; Smith, Richard D. J.; von Keudell, Gottfried R.; Smith, Malcolm R.; Weaver, Michael J.; Nazarian, Ara; von Keudell, Arvind G.
Abstract : Objective: To characterize the patient population with substance-related found-down extremity compartment syndrome (FDECS) and report on their treatment and outcome. Data Source: This systematic review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Articles in English language were identified by searching 3 online databases, EMBASE, PubMed Publisher, and Cochrane Central, in September 2019. Study Selection: Studies involving substance-related FDECS were included. Exclusion criteria were as follows: patient age <18 years, not original studies, no full text available, technical reports, traumatic acute extremity compartment syndrome, chronic exertional compartment syndrome, and vascular acute extremity compartment syndrome. Data Extraction: There were 61 studies included with 166 cases of FDECS. Two investigators screened and extracted data independently according to a standardized template. Disagreements were addressed by an attempt to reach a consensus, and involvement of a third reviewer. Studies were quality assessed with "Quality Assessment tool for Case Series Studies." Data Synthesis: Descriptive statistics were reported using Excel. Conclusion: Substance-related FDECS is often occurring in young adults. Data from this review found that most of the patients were already diagnosed with substance use disorders and/or psychiatric disorders. There should be a high index of suspicion of FDECS in patients presenting after prolonged immobilization. Level of Evidence: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.